2011 2nd International Conference on Artificial Intelligence, Management Science and Electronic Commerce (AIMSEC) 2011
DOI: 10.1109/aimsec.2011.6011451
|View full text |Cite
|
Sign up to set email alerts
|

The B2C group-buying model on the Internet

Abstract: Internet-based group-buying has become a new growth point for China's e-commerce. By studying B2C groupbuying model, this paper has collected data of 20 major Chinese group-buying websites, studied factors that might influence Internet users' group-buying behavior, proposed a new model for evaluating the value of Internet enterprises, and provided a feasible reference model for the evaluation and performance of Internet enterprises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The other group studying the design perspective of FPGB includes Byers et al (2011), Liu and Sutanto (2012), Song (2011), andZhou et al (2013). Byers et al (2011) showed the operational strategies of Groupon.com through design factors such as a primary buying incentive (e.g., price) and soft incentives (e.g., deal scheduling and duration, deal featuring, and limited inventory).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other group studying the design perspective of FPGB includes Byers et al (2011), Liu and Sutanto (2012), Song (2011), andZhou et al (2013). Byers et al (2011) showed the operational strategies of Groupon.com through design factors such as a primary buying incentive (e.g., price) and soft incentives (e.g., deal scheduling and duration, deal featuring, and limited inventory).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it insisted that FPGB might utilize not only the primary buying incentive but also the soft incentives for optimizing deal designs. Song (2011) analyzed which design factors affected consumers' FPGB behavior. According to its analysis results, most design factors of FPGB such as price, discount, group buying time, group buying people volume, and website brand were significant to consumer's FPGB intention.…”
Section: Introductionmentioning
confidence: 99%